2018
DOI: 10.1128/aem.02749-17
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Metabolomics and Morphogenesis Reveal Volatile Signaling of the Nematode-Trapping Fungus Arthrobotrys oligospora

Abstract: The adjustment of metabolic patterns is fundamental to fungal biology and plays vital roles in adaptation to diverse ecological challenges. Nematode-trapping fungi can switch their lifestyle from saprophytic to pathogenic by developing specific trapping devices induced by nematodes to infect their prey as a response to nutrient depletion in nature. However, the chemical identity of the specific fungal metabolites used during the switch remains poorly understood. We hypothesized that these important signal mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 51 publications
3
39
0
4
Order By: Relevance
“…NTF hold great potential as biocontrol agents to target parasitic nematodes, and, thus, are a subject of interest to scientists. The interactions between NTF and their nematode prey have been studied for several decades, but the underlying molecular mechanisms only began to be revealed in the more recent years [5,[9][10][11]13]. In this study, we have further expanded our understanding of the metabolites of a hundred strains of Arthrobotrys NTF by metabolomic analyses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NTF hold great potential as biocontrol agents to target parasitic nematodes, and, thus, are a subject of interest to scientists. The interactions between NTF and their nematode prey have been studied for several decades, but the underlying molecular mechanisms only began to be revealed in the more recent years [5,[9][10][11]13]. In this study, we have further expanded our understanding of the metabolites of a hundred strains of Arthrobotrys NTF by metabolomic analyses.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, little is known about the metabolome of NTF. Previous studies have shown that A. oligospora produces volatile organic compounds (VOCs) that mimic sex and food cues to attract the nematode prey in the absence of nematodes [10], and a more recent study also reported VOCs produced by A. oligospora during the predation process [11]. Nonetheless, the metabolites produced by NTF induced by the nematode prey during predation remained largely unexplored.To gain more insights into how NTF response to nematode prey during predation, we analyzed the metabolites of 100 wild isolates of three different NTF species, Arthrobotrys oligospora, Arthrobotrys thaumasia, and Arthrobotrys musiformis, which were all collected in Taiwan [12] (Figure 1a,b; Table S1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These two media differ in their capacities to induce traps. A compound, maltol, was isolated and shown to be able to stimulate trap formation in A. oligospora [28]. Together, these studies identified many signal molecules and several signal transducers capable of inducing fungal trap formation.…”
Section: (Iv) Signals From Secondary Metabolitesmentioning
confidence: 90%
“…Under nitrogen starvation, ascaroside-induced morphogens are required for A. oligospora to sense and initiate trap formation in response to the availability of nematode prey [ 24 , 141 ]. Recent studies have also characterized several other morphology-regulating arthrosporol metabolites from A. oligospora and identified them as important signaling cues for hyphal development, nematode attraction, and trap morphogenesis [ 29 , 62 , 142 ].…”
Section: Fungi and Nematodes Interact Through A Third Partymentioning
confidence: 99%